Thin-walled effect of microstructure of third-generation single crystal superalloy DD9 - YANG Wanpeng; LI Jiarong; LIU Shizhong; ZHAO Jinqian; WANG Xiaoguang; YANG Liang; WANG Rui; CHEN Qiao (Cailiao gongcheng)
The microstructure and thin-walled effect of different samples （double-wall ultra-cooling turbine blades， combined cooling turbine blades， investment casting thin-walled specimen， and round bar specimen） of the third-generation single crystal superalloy DD9 are investigated by optical microscope， field emission scanning electron microscope， and electron probe apparatus. The results show that there are differences in the microstructures of the four specimens. When the section sizes are the same， the as-cast primary dendrite arm spacing， the sizes of γ′ phases， and the dendrite segregation of the as-cast and heat- treated specimens of DD9 single crystal turbine blades are all larger than those of the investment casting thin-walled specimens. After full heat treatment， the sizes of the γ′ phases of single crystal turbine blades with the same cross-sectional size are similar to those of investment casting thin-walled specimens. The as-cast primary dendrite arm spacing， the sizes of γ′ phases， and the dendrite segregation of the as-cast and heat-treated thin-walled specimens of DD9 alloy all decrease with the decrease of the cross-sectional size.